Fungal glyceraldehyde 3-phosphate dehydrogenase GpdC maintains glycolytic mechanism against reactive nitrogen stress-induced damage - Kadooka, Chihiro; Katsuki, Nozomi; Masuo, Shunsuke; Kojima, Saito; Amahisa, Madoka; Suzuki, Kouta; Doi, Yuki; Takeshita, Norio; Takaya, Naoki (Frontiers in Microbiology, 2024)
Highly reactive nitrogen species (RNS) damage proteins, lipids, and nucleotides, and induce disordered intracellular metabolism. Microorganisms that respond to and defend against RNS include fungal pathogens that invade host tissues. However, the full picture of their mechanisms remains unknown. We identified a novel glyceraldehyde 3-phosphate dehydrogenase (GAPDH) isozyme (GpdC) in the fungus Aspergillus nidulans. This isozyme preferred NADP + , which was unlike glycolytic GpdA that uses NAD + as a cofactor. Exogenous RNS induced expression of the encoding gpdC gene, which when disrupted, decreased intracellular GAPDH activity, mycelial proliferation, and ethanol fermentation under RNS stress. Under these conditions, fungal growth requires glucose instead of non-fermentable carbon sources, and intact pyruvate decarboxylase (pdcA) and alcohol dehydrogenase (alcC) genes indicated that fungal metabolism shifts from respiratory to glycolytic and ethanolic fermentation. These results indicated that GpdC is an alternative GAPDH isozyme that facilitates NADP + -dependent glycolysis and energy conservation, which constitutes a fungal mechanism of stress tolerance via metabolic adaptation.